Preliminary investigation of gut microbiota and associated metabolic pathways in the pathogenesis of primary central nervous system lymphoma - Kang, Zhuang; Zhang, Rong; Li, Shenglan; Wang, Jiachen; Huang, Mengqian; Li, Wenbin (Frontiers in Oncology, 2025)
BackgroundPrimary central nervous system lymphoma (PCNSL) is a rare and highly aggressive form of non-Hodgkin lymphoma, primarily confined to the central nervous system. In recent years, growing evidence has indicated that dysbiosis of the gut microbiota is closely associated with the development of various malignancies. This study aims to systematically explore the potential role of gut microbiota and their metabolic pathways in the pathogenesis of PCNSL by integrating metagenomic and metabolomic approaches.Materials and methodsA total of 33 PCNSL patients and 32 healthy controls were enrolled in this study, and fecal samples were collected from each participant. The fecal samples were analyzed using metagenomic and metabolomic techniques, followed by KEGG pathway enrichment analysis to investigate the biological pathways enriched by the differential gut microbiota and metabolites.ResultsSignificant differences were observed in the composition of gut microbiota and metabolites between PCNSL patients and healthy controls. In the gut microbiota of PCNSL patients, the abundance of the phylum Proteobacteria was markedly increased, while the Firmicutes/Bacteroidetes (F/B) ratio was significantly elevated. Metabolomic analysis revealed that the abundance of oleamide was significantly reduced in the PCNSL group, while the relative abundance of deoxycholic acid was significantly elevated. KEGG pathway analysis indicated that the differential gut microbiota and metabolites were primarily involved in key metabolic pathways such as nitrogen metabolism, phenylalanine metabolism, purine metabolism, and pyrimidine metabolism, with these pathways being more active in PCNSL patients.ConclusionThis study is the first to systematically investigate the differences in gut microbiota and their metabolites between PCNSL patients and healthy individuals, highlighting the potential role of gut microbiota alterations in the pathogenesis of PCNSL.